POVERTY AND UNEMPLOYMENT EFFECTS ON FEMALE CRIMINAL BEHAVIOR IN PUNJAB PAKISTAN - Hafiza Ayesha Saeed; Dr Zahira Batool; Dr Babak Mahmood; Dr Ayesha Chaudhary (International Journal of Contemporary Issues in Social Sciences, 2024)
The main objective of this research was to explore the different factors affecting criminal behavior in Punjab, Pakistan. A multistage sampling technique was used for a sample of 300 respondents who have ever committed a crime. A well designed interview schedule was used to conduct data from the Prisoners. District and central jails were selected for data collection. For the Evaluation of data quantitatively using descriptive statistics (frequencies and percentages) and by inferential statistics (Chi-square and logistic regression model) mainly based on respondents’ perceptions. Data was evaluated quantitatively using descriptive statistics (frequencies and percentages) and by inferential statistics (Chi-square and logistic regression model). According to descriptive analysis young and married people were more than. Almost one fourth population were illiterate, while 30% of the majority were unemployed. 19-30 age group of people were crime first at this age. Almost 43% people involve in crimes with friend’s interaction. There was highly association between poverty unemployment and crimes. Unemployment, Poverty, Broken homes, Peer Group and multiple other factors are also the reasons behind the criminal acts and behavior. Findings of this study suggest that more economic opportunities will help reduce the unemployment rate, resultantly decreasing the crime rate in specific settings. Parents should keep their eyes on friends of their children; also, they should create a healthy and friendly. Opportunities of jobs, end funds for education can also control the female criminal behavior in Pakistan.